Association of diabetes mellitus with disease severity and prognosis in COVID-19: A retrospective cohort study. (July 2020) - Zhang, Yan; Cui, Yanhui; Shen, Minxue; Zhang, Jianchu; Liu, Ben; Dai, Minhui; Chen, Lingli; Han, Duoduo; Fan, Yifei; Zeng, Yanjun; Li, Wen; Lin, Fengyu; et al.
Abstract: Aims: The 2019 novel coronavirus disease (COVID-19) emerged in Wuhan, China, and was characterized as a pandemic by the World Health Organization. Diabetes is an established risk associated with poor clinical outcomes, but the association of diabetes with COVID-19 has not been reported yet. Methods: In this cohort study, we retrospectively reviewed 258 consecutive hospitalized COVID-19 patients with or without diabetes at the West Court of Union Hospital in Wuhan, China, recruited from January 29 to February 12, 2020. The clinical features, treatment strategies and prognosis data were collected and analyzed. Prognosis was followed up until March 12, 2020. Results: Of the 258 hospitalized patients (63 with diabetes) with COVID-19, the median age was 64 years (range 23–91), and 138 (53.5%) were male. Common symptoms included fever (82.2%), dry cough (67.1%), polypnea (48.1%), and fatigue (38%). Patients with diabetes had significantly higher leucocyte and neutrophil counts, and higher levels of fasting blood glucose, serum creatinine, urea nitrogen and creatine kinase isoenzyme MB at admission compared with those without diabetes. COVID-19 patients with diabetes were more likely to develop severe or critical disease conditions with more complications, and had higher incidence rates of antibiotic therapy, non-invasive and invasive mechanical ventilation, and death (11.1% vs. 4.1%). Cox proportional hazard model showed that diabetes (adjusted hazard ratio [aHR] = 3.64; 95% confidence interval [CI]: 1.09, 12.21) and fasting blood glucose (aHR = 1.19; 95% CI: 1.08, 1.31) were associated with the fatality due to COVID-19, adjusting for potential confounders. Conclusions: Diabetes mellitus is associated with increased disease severity and a higher risk of mortality in patients with COVID-19.